2013
DOI: 10.4103/0253-7184.120542
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal and rheumatological disorders in HIV infection: Experience in a tertiary referral center

Abstract: Background:Musculoskeletal involvement in human immunodeficiency virus (HIV) infected patients are important disease manifestations, responsible for increased morbidity and also decreased quality of life.Objectives:To study the spectrum of different musculoskeletal involvement in HIV infected patients and its impact on quality of life.Patients and Methods:Three hundred (n = 300) HIV-1 reactive patients were evaluated in respect to different musculoskeletal involvement including the quality of life from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 11 publications
(10 reference statements)
0
46
1
3
Order By: Relevance
“…It has long been held that Lyme disease increases the risk of FMS, but a recent study showed that the incidence of FMS in patients with cultureconfirmed Lyme disease did not exceed that of the general population during long-term follow-up [405]. The results for other infectious agents also are far from consistent [403,406,407]. This suggests that, if infectious agents act as triggers for FMS at all, this process is relevant in a subset of patients only.…”
Section: Cytokinesmentioning
confidence: 99%
“…It has long been held that Lyme disease increases the risk of FMS, but a recent study showed that the incidence of FMS in patients with cultureconfirmed Lyme disease did not exceed that of the general population during long-term follow-up [405]. The results for other infectious agents also are far from consistent [403,406,407]. This suggests that, if infectious agents act as triggers for FMS at all, this process is relevant in a subset of patients only.…”
Section: Cytokinesmentioning
confidence: 99%
“…По этой причине наличие симметричного и в ряде случаев деструктивного полиартрита у больных ВИЧ-инфекцией нередко классифицировали как «ревматои-доподобный» артрит [32]. В эпоху ВААРТ стала общепри-знанной возможность наличия «истинного» РА у больных ВИЧ-инфекцией с частотой 0,1-5% [13,[33][34][35][36]. В ходе мультицентрового когортного исследования, выполнен-ного французскими авторами, выявлено 46 больных РА в сочетании с ВИЧ-инфекцией.…”
Section: ревматологияunclassified
“…Musculoskeletal disorders in patients with HIV may be due to a direct effect of the virus, opportunistic infections, or noninfectious complications of HIV infection or its therapy [78,79]. Various conditions can be seen in the setting of HIV, including painful articular syndrome, reactive arthritis, HIV-associated arthritis, rheumatoid arthritis, hypertrophic osteoarthropathy, acute gout, avascular bone necrosis, septic arthritis, and osteomyelitis [80,81]. Similar to HIV-negative patients, septic arthritis occurring in HIV-infected patients is most commonly due to S. aureus [82,83].…”
Section: Microbiologymentioning
confidence: 99%